Analisis Yuridis Penyelesaian Tindak Pidana Pencurian Arus Listrik di PT Perusahaan Listrik Negara: Persero Unit Layanan Pelanggan Tanjungbalai - Silmi Kaffah; Farid Wajdi (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The increasing human need for electricity has led to an increase in various modes of electricity theft. The aim of this research was to determine the resolution of the crime of electric current theft at PT PLN Tanjungbalai city. The research method used is a normative juridical legal research method (normative law research), namely a legal research method by examining the implementation or implementation of positive legal provisions (legislation) and factual contracts in every legal event and achievement of goals in society. The data collection technique uses literature review as secondary data by discussing Law Number 30 of 2009 concerning Electricity and interviews as primary data to determine the resolution and prevention of acts of electricity theft in the city of Tanjungbalai. The steps taken by PT. PLN Tanjungbalai City in resolving the criminal act of electricity theft are based on the provisions stated in PT. PLN Directors Regulation Number 0028 to provide a deterrent effect and fear to the individuals who carry out the theft. PT. PLN Tanjungbalai city also carries out prevention by providing outreach about electricity to the community as an effort to increase understanding and awareness of sanctions for committing violations.